Effects of contract termination for breach of contract: restitution and damages in a comparative perspective within the legal latinity - Nicolussi, Andrea (2023)
The essay addresses the restitutions derived from the resolution for non-compliance in a comparative way within the “legal Latinity”. It compares the solutions accepted in Italian law (European legal latinity), and those of two Latin American legal systems, Colombia, and Peru. From the point of view of the discipline dedicated to resolution (termination) and its consequences, the Italian and Peruvian codes are the most advanced, while the Colombian one, which dates from the nineteenth century, leaves ample room for the jurisprudential development of this remedy. In any event, the three legal systems seem to converge on the role of restitution as a tool to return the parties to the economic situation prior to the contract. However, with regard to the basis of the restitution function, uncertainties persist between the condictio indebiti and restitutions specifically regulated in the framework of rhe resolution (termination). Even the reciprocal link between the restitutions owed by the two parties remains undeepened. Finally, the coordination between restitution and compensation for damages in the context of the resolution seems to be more clearly captured in the Italian doctrine, to which the Peruvian doctrine seems closer. Damages must be compatible with the fact that the fullfilling party of the contract no longer owes its observance to the contract, and waives the consideration. Damages cannot therefore include the value of the performance unfulfilled, but must protect the party who is faithful to the contract in terms of its positive interest in the contract, that is to say, the benefit that he would have obtained by using the performance due if it had been fulfilled.